Quantitative and Qualitative Changes of Bone in Psoriasis and Psoriatic Arthritis Patients. (10th May 2015) - Kocijan, Roland; Englbrecht, Matthias; Haschka, Judith; Simon, David; Kleyer, Arnd; Finzel, Stephanie; Kraus, Sebastian; Resch, Heinrich; Muschitz, Christian; Engelke, Klaus; Sticherling, Michael; Rech, Jürgen; et al.
ABSTRACT: Psoriatic arthritis (PsA) is a chronic inflammatory disease characterized by periarticular bone loss and new bone formation. Current data regarding systemic bone loss and bone mineral density (BMD) in PsA are conflicting. The aim of this study was to evaluate bone microstructure and volumetric BMD (vBMD) in patients with PsA and psoriasis. We performed HR‐pQCT scans at the ultradistal and periarticular radius in 50 PsA patients, 30 psoriasis patients, and 70 healthy, age‐ and sex‐related controls assessing trabecular bone volume (BV/TV), trabecular number (Tb.N), inhomogeneity of the trabecular network, cortical thickness (Ct.Th), and cortical porosity (Ct.Po), as well as vBMD. Trabecular BMD (Tb.BMD, p  = 0.021, 12.0%), BV/TV ( p  = 0.020, –11.9%), and Tb.N ( p  = 0.035, 7.1%) were significantly decreased at the ultradistal radius and the periarticular radius in PsA patients compared to controls. In contrast, bone architecture of the ultradistal radius and periarticular radius was similar in patients with psoriasis and healthy controls. Duration of skin disease was associated with low BV/TV and Tb.N in patients with PsA. These data suggest that trabecular BMD and bone microstructure are decreased in PsA patients. The observation that duration of skin disease determines bone loss in PsA supports the concept of subclinical musculoskeletal disease in psoriasis patients. © 2015 American Society for Bone and Mineral Research.